SOCIALIZATION OF MORINGA LEAF PUDDING MAKING AS EFFORT TO PREVENT STUNTING IN BENDO HAMLET - Rahmadhanti; Novita Adhe Wardany; Hasna Nur Iriyanti; Alfi Sukri; Wahyu Aminudin (UIN Sunan Kalijaga, 2025)
Abstract - Stunting is a major health problem in Indonesia that threatens the quality of future generations. This condition is primarily caused by chronic malnutrition, especially insufficient intake of protein and essential micronutrients. One potential effort to address this issue is the use of moringa leaves, which are highly nutritious and locally available. This study aims to describe the implementation of socialization on moringa leaf pudding as an innovative supplementary food to prevent stunting in Bendo Hamlet. The research employed a Community-Based Research (CBR) approach that involved KKN students, posyandu cadres, PKK mothers, and mothers of toddlers in a participatory process from planning to evaluation. The findings showed improvements in community knowledge about the nutritional benefits of moringa leaves, enhanced skills in preparing pudding, and positive acceptance of the product among children. Acceptance was influenced by the pudding’s soft texture, balanced sweetness, and attractive natural green color. The success of the program was also supported by easy access to raw materials, a simple preparation method, and strong cadre commitment. Thus, moringa leaf pudding can serve as a practical and sustainable local food alternative to help fulfill children’s nutritional needs while strengthening family food security. Keyword: Moringa Leaves, Moringa Leaf Pudding, Local Food, Stunting Prevention. Abstrak - Stunting merupakan salah satu masalah kesehatan yang masih menjadi perhatian di Indonesia karena berdampak pada kualitas generasi mendatang. Kondisi ini disebabkan oleh kurangnya asupan gizi kronis, terutama protein dan mikronutrien penting. Salah satu upaya yang dapat dilakukan adalah pemanfaatan daun kelor sebagai bahan pangan lokal bergizi tinggi. Penelitian ini bertujuan untuk mendeskripsikan implementasi sosialisasi pembuatan puding daun kelor sebagai inovasi pangan tambahan dalam pencegahan stunting di Dusun Bendo. Penelitian menggunakan pendekatan Community-Based Research (CBR) yang melibatkan mahasiswa KKN, kader posyandu, ibu PKK, dan ibu balita secara partisipatif mulai dari perencanaan hingga evaluasi. Hasil penelitian menunjukkan adanya peningkatan pengetahuan masyarakat mengenai manfaat gizi daun kelor, keterampilan dalam mengolah puding, serta penerimaan positif dari anak-anak terhadap produk tersebut. Faktor penerimaan dipengaruhi oleh tekstur lembut, rasa manis yang seimbang, serta warna hijau alami yang menarik. Keberhasilan kegiatan ini juga didukung oleh kemudahan memperoleh bahan baku, proses pembuatan yang sederhana, serta komitmen kader posyandu dalam melanjutkan praktik. Dengan demikian, puding daun kelor berpotensi menjadi alternatif pangan lokal yang tidak hanya membantu pemenuhan gizi anak, tetapi juga memperkuat ketahanan pangan keluarga serta mendukung upaya berkelanjutan dalam pencegahan stunting. Kata kunci: Daun Kelor, Puding Daun Kelor, Pangan Lokal, Pencegahan Stunting.